Epoxy resin coating resistant to chemical corrosion and preparation method thereof

By modifying the composite structure of nanoparticles and epoxy resin, the problems of chemical degradation and moisture penetration of traditional epoxy resin coatings in extreme environments are solved, achieving high-strength bonding and excellent waterproof and moisture-proof performance, and improving the aging resistance and stability of the coating.

CN119264785AActive Publication Date: 2025-01-07DEZHOU VOCATIONAL & TECHN COLLEGE

Patent Information

Application Number
CN202411696147.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Traditional epoxy resin coatings are prone to chemical degradation or physical damage in environments with strong acids, strong alkalis, or organic solvents. They have limited waterproof and impermeable capabilities and cannot effectively prevent moisture penetration, thus affecting the long-term stability and reliability of the coating.

Method used

The composite structure of modified nanoparticles and a specific epoxy resin composition is adopted. Spherical particles are formed through the coating effect of titanium dioxide and amorphous silica, which enhances the stability of nanoparticles in the coating and the ability to guide water molecules. Combined with surface hydrogen bonding, the adhesion is improved, high-strength connection is formed, micropores are reduced, and waterproof, moisture-proof and aging-resistant properties are achieved.

Benefits of technology

It significantly improves the coating's resistance to chemical corrosion, water and moisture, and aging, avoids water molecule penetration and the segregation and migration of modified particles, and ensures the stability and long-term performance of the coating in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of coatings, in particular to a chemical corrosion resistant epoxy resin coating and a preparation method thereof. The epoxy resin coating resistant to chemical corrosion comprises the following raw materials in parts by mass: 80-100 parts of an epoxy resin composition, 15-25 parts of a curing agent, 15-25 parts of modified nanoparticles, 2-5 parts of an anti-settling agent, 1-3 parts of a flatting agent, 1-2 parts of a defoaming agent, 5-10 parts of pigment filler and 20-40 parts of a diluent. The epoxy resin coating prepared by the invention not only has excellent binding power, but also can maintain excellent chemical corrosion resistance, water resistance, moisture resistance, aging resistance and the like, and can meet the performance requirements of various industries in the prior art on the epoxy resin coating, so that the application of the epoxy resin coating is greatly expanded, and the epoxy resin coating has very excellent application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coatings, and in particular to an epoxy resin coating resistant to chemical corrosion and a preparation method thereof. Background Art

[0002] With the development of industrial technology, the requirements for chemical resistance, corrosion resistance and mechanical properties of materials are getting higher and higher. Especially in the fields of chemical, pharmaceutical, marine engineering, etc., equipment and structural parts are often exposed to harsh chemical environments, so protective coatings that can effectively resist corrosion from various chemicals are needed to extend their service life and ensure safe operation.

[0003] Epoxy resin coatings are widely used in the above-mentioned fields due to their excellent adhesion, chemical resistance and good mechanical strength. Epoxy resin is a thermosetting polymer that forms a three-dimensional network structure by reacting with a curing agent, thereby providing excellent physical and chemical properties. However, as the application environment becomes increasingly harsh, traditional epoxy resin coatings still have shortcomings under certain extreme conditions. For example, in highly corrosive environments such as strong acids, strong alkalis or solvents, traditional epoxy resin coatings may swell, dissolve or delaminate, resulting in a decrease in protective effect. In addition, some high-performance chemicals may penetrate into the coating, destroying the bond between the coating and the substrate, further affecting the long-term stability and reliability of the coating.

[0004] Although the epoxy resin coatings currently available on the market can meet the requirements of use in most cases, there are still the following problems when facing extreme chemical corrosion. For example, in specific strong acid, strong alkali or organic solvent environments, traditional epoxy resin coatings may not be able to maintain their integrity and are prone to chemical degradation or physical damage, resulting in failure of the protective function; the waterproof and anti-penetration capabilities are limited. For certain highly permeable environments, existing epoxy resin coatings may not be able to effectively prevent moisture and solutions with moisture as the carrier from penetrating the coating, thereby causing aging and corrosion of the substrate.

[0005] Therefore, in order to effectively solve the above problems, the present application provides an epoxy resin coating resistant to chemical corrosion and a preparation method thereof. The epoxy resin coating prepared in the present application not only has excellent adhesion, but also can maintain excellent chemical corrosion resistance, waterproofness, moisture resistance and aging resistance. The performance requirements of various industries for epoxy resin coatings can be met, thereby greatly expanding the application of epoxy resin coatings, and thus having very excellent application value. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides an epoxy resin coating resistant to chemical corrosion. The raw materials are, by mass: 80 to 100 parts of epoxy resin composition, 15 to 25 parts of curing agent, 15 to 25 parts of modified nanoparticles, 2 to 5 parts of anti-settling agent, 1 to 3 parts of leveling agent, 1 to 2 parts of defoaming agent, 5 to 10 parts of color filler, and 20 to 40 parts of diluent.

[0007] As a preferred solution, the mass ratio of the epoxy resin composition, the curing agent and the modified nanoparticles is (85-95): (18-22): (20-24).

[0008] As a preferred embodiment, the mass ratio of the epoxy resin composition, the curing agent and the modified nanoparticles is (88-94): (18-20): (22-24).

[0009] As a preferred solution, the epoxy resin composition is a composition of bisphenol A epoxy resin, epoxy block resin and modified epoxy resin.

[0010] As a preferred solution, the mass ratio of the bisphenol A epoxy resin, epoxy block resin and modified epoxy resin is (60-70): (10-15): (10-15).

[0011] As a preferred solution, the mass ratio of the bisphenol A epoxy resin, epoxy block resin and modified epoxy resin is (65-70): (10-12): (14-15).

[0012] As a preferred solution, the epoxy equivalent of the bisphenol A epoxy resin is 220-240 g / eq.

[0013] As a preferred solution, the viscosity of the bisphenol A epoxy resin is 8000-12000 mPa·s at 25°C.

[0014] As a preferred solution, the epoxy block resin is an ethylene oxide-propylene oxide block copolymer resin.

[0015] As a preferred solution, the weight average molecular weight of the epoxy block resin is 2000~4000Da.

[0016] As a preferred solution, the ethylene oxide block content of the epoxy block resin is 30-35wt%.

[0017] As a preferred solution, the preparation method of the modified epoxy resin specifically includes the following steps: S1: adding the base epoxy resin to a reaction kettle with a stirring device, heating it to 80-90°C to make it completely melted, and then adding DMF and continuing to stir until it is evenly mixed; S2: slowly adding 4,4'-diaminodiphenyl ether while stirring at a speed of 80-100rpm, and continuing to stir for 30-35min after the addition is completed; S3: adding triethylamine, maintaining the temperature at 85-95°C, and continuing to stir the reaction for 2-4h. After the reaction is completed, stop heating, let the mixture cool naturally to room temperature, and pass the obtained product through a 400-600 mesh sieve to remove unreacted solid particles and other impurities, and then transfer it to a clean container, seal it and store it to avoid contact with air and moisture.

[0018] As a preferred solution, the base epoxy resin is E-51 or E-44.

[0019] As a preferred solution, the mass ratio of the matrix epoxy resin, 4,4'-diaminodiphenyl ether and triethylamine is (60-70): (10-20): (0.5-1).

[0020] As a preferred solution, the preparation method of the modified nanoparticles specifically comprises the following steps: S1: titanium dioxide and zinc nitrate hexahydrate are mixed and added to DMF, glutaric anhydride and tetraisopropoxy titanate are added, the temperature is raised to 75-80°C and kept warm for 2-2.5 hours, then ammonia water is added to adjust the pH to 8-8.5, then triethylamine, ethyl orthosilicate and ethanol are added, and the temperature is kept at 60-65°C for 1.5-2 hours. After the reaction is completed, the product is filtered and washed to obtain pre-modified particles; S2: the pre-modified particles are added to DMF and mixed The mixture was stirred at 50-60 rpm for 20-30 min until uniform, and then the temperature was raised to 80-90 °C and kept warm for 1-1.5 h. The DMF solution containing 1,4-diaminobenzene was then added dropwise for 1-1.5 h. After completion, the reaction vessel was heated uniformly from 3-4 °C to 110-130 °C and kept warm for 14-16 h. After the reaction was completed, it was naturally cooled to room temperature and the product was filtered, washed with deionized water and acetone for 2-3 times, and dried in a vacuum oven at 70-80 °C.

[0021] As a preferred solution, the mass ratio of titanium dioxide, zinc nitrate hexahydrate, glutaric anhydride and tetraisopropoxy titanate is (1.5-2): (4-5): (1.5-2): (0.2-0.4).

[0022] As a preferred solution, the mass ratio of titanium dioxide, zinc nitrate hexahydrate, triethylamine and ethyl orthosilicate is (1.5-2): (4-5): (0.05-0.1): (0.4-0.5).

[0023] As a preferred solution, in the pre-modified particles, the mass ratio of 1,4-phthalic acid to 1,4-diaminobenzene is (3-4): (1.8-2.2): (0.6-0.8).

[0024] As a preferred solution, the average particle size of the titanium dioxide is 10-15 nm; the average particle size of the modified nanoparticles is 550-650 nm.

[0025] The modified nanoparticles prepared in the present application can effectively improve the aging resistance, corrosion resistance, and waterproof and moisture resistance of epoxy resin coatings. The modified nanoparticles can form spherical particles through the coating of titanium dioxide and amorphous silicon dioxide, and realize the embedding of tiny nanoparticles on the surface of the framework structure. The formation of the composite structure can greatly improve the guiding effect of the nanoparticles on water molecules, thereby directly guiding water molecules to the structure of the framework particles for absorption in the early stage of contact with water. The absorption effect does not desorb at the ambient temperature of daily use, and after adsorption saturation, it can form a barrier with external water molecules through the surface particle coating, thereby directly removing the water molecules and active groups that penetrate into the surface in the early stage of the coating contacting the high humidity environment, thereby realizing the isolation of water molecules on the coating surface, avoiding the formation of water molecule penetration channels, and failing to form a continuous hydration layer on the coating surface, thereby obtaining excellent chemical resistance and waterproof and moisture resistance.

[0026] On the other hand, the modified nanoparticles prepared in the present application can achieve high-strength connection with the specific epoxy resin composition added in the present application through surface hydrogen bonding in the coating system, thereby greatly enhancing the stability of the modified nanoparticles in the coating system, avoiding the segregation and migration of the modified particles under long-term use of the coating and in extreme environments, and can also greatly reduce the micropores occupied by the modified nanoparticles, reduce the shaking of the nanoparticles, and maintain excellent particle stability in active environments such as high temperature and high humidity, thereby obtaining excellent coating aging resistance.

[0027] As a preferred solution, the anti-settling agent is at least one of fumed silica, hydrogenated castor oil, organic bentonite and polyamide wax.

[0028] As a preferred solution, the anti-settling agent is hydrogenated castor oil.

[0029] As a preferred solution, the leveling agent is at least one of an organic silicone leveling agent, a polyacrylate leveling agent, a polyether modified silicone oil leveling agent and a polyester leveling agent.

[0030] As a preferred solution, the leveling agent is any one of the organic silicon leveling agents.

[0031] As a preferred solution, the defoaming agent is at least one of silicone defoaming agents.

[0032] As a preferred solution, the pigment filler is any one of titanium dioxide, iron oxide, carbon black, phthalocyanine blue, permanent red and ultramarine.

[0033] As a preferred solution, the pigment filler is phthalocyanine blue or titanium dioxide.

[0034] As a preferred solution, the diluent is a combination of xylene and ethylene glycol monobutyl ether.

[0035] As a preferred solution, the mass ratio of xylene to ethylene glycol monobutyl ether is (5-6): (1.5-2.5).

[0036] As a preferred solution, the mass ratio of xylene to ethylene glycol monobutyl ether is (5-5.5): (1.6-2.2).

[0037] The second aspect of the present application provides a method for preparing the above-mentioned epoxy resin coating resistant to chemical corrosion, which specifically comprises the following steps: S1: adding the epoxy resin composition to a reactor with a stirring device, heating to 80-90°C, stirring continuously at 80-120rpm until it is completely melted and uniform, and slowly adding modified nanoparticles, anti-settling agent, leveling agent and defoaming agent under stirring and continuing stirring for 30-40min to ensure that all solid particles are fully dispersed; S2: after adding the pigment and filler, stirring at a high speed of 400-600rpm for 60-80min; S3: cooling to room temperature, slowly adding the curing agent, and stirring continuously for 20-30min, and finally adding the diluent to mix the coating, and after completion, passing through a 400-600 mesh sieve, filling the obtained product into a container and sealing it for storage.

[0038] The beneficial effects of this application are: 1. The present application provides a chemical-resistant epoxy resin coating, which not only has excellent adhesion, but also can maintain excellent chemical corrosion resistance, water resistance, moisture resistance and aging resistance, etc., and can meet the performance requirements of various industries for epoxy resin coatings, thereby greatly expanding the application of epoxy resin coatings, and thus has very excellent application value.

[0039] 2. The present application provides an epoxy resin coating resistant to chemical corrosion, wherein the modified nanoparticles added thereto can form spherical particles through the coating effect of titanium dioxide and amorphous silicon dioxide, thereby realizing the embedding of tiny nanoparticles on the surface of the framework structure. The formation of the composite structure can greatly improve the guiding effect of the nanoparticles on water molecules, thereby directly guiding the water molecules to the structure of the framework particles for absorption in the early stage of contact with water. The absorption effect does not desorb at the ambient temperature of daily use, and after adsorption saturation, it can form a barrier with external water molecules through the surface particle coating, thereby directly removing the water molecules and active groups that penetrate into the surface in the early stage of the coating contacting the high humidity environment, thereby realizing the isolation of water molecules on the coating surface, avoiding the formation of water molecule penetration pathways, and failing to form a continuous hydration layer on the coating surface, thereby achieving excellent chemical resistance and waterproof and moisture resistance.

[0040] 3. The present application provides an epoxy resin coating resistant to chemical corrosion, in which the modified nanoparticles added can also achieve high-strength connection with the specific epoxy resin composition added in the present application through surface hydrogen bonding in the coating system, thereby greatly enhancing the stability of the modified nanoparticles in the coating system, avoiding the segregation and migration of the modified particles under long-term use of the coating and in extreme environments, and can also greatly reduce the micropores occupied by the modified nanoparticles, reduce the shaking of the nanoparticles, and thus maintain excellent particle stability in active environments such as high temperature and high humidity, thereby obtaining excellent coating aging resistance. DETAILED DESCRIPTION

[0041] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0042] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0043] Example 1: Example 1 The first aspect provides an epoxy resin coating resistant to chemical corrosion. The raw materials are, by mass: 90.8 parts of epoxy resin composition, 19.5 parts of curing agent, 23.2 parts of modified nanoparticles, 4.2 parts of anti-settling agent, 1.8 parts of leveling agent, 1.2 parts of defoaming agent, 8.5 parts of color filler, and 25 parts of diluent.

[0044] The epoxy resin composition is a composition of bisphenol A epoxy resin, epoxy block resin and modified epoxy resin, and the mass ratio of the three is 66:10:14.8.

[0045] The epoxy equivalent of bisphenol A epoxy resin is 230 g / eq and the viscosity is 9500 mPa·s at 25° C. It is purchased from the Epon series products with corresponding parameters sold by Hanson, USA.

[0046] The epoxy block resin is an ethylene oxide-propylene oxide block copolymer resin with a weight average molecular weight of 3000 Da and an ethylene oxide block content of 35 wt %, and is purchased from the L64 model product sold by BASF in Germany.

[0047] The preparation method of the modified epoxy resin specifically includes the following steps: S1: adding 65 parts of base epoxy resin E-44 into a reactor with a stirring device, heating to 90°C to make it completely melted, and then adding 450 parts of DMF and continuing to stir until it is evenly mixed; S2: slowly adding 16.5 parts of 4,4'-diaminodiphenyl ether with stirring at a speed of 90rpm, and continuing to stir for 30 minutes after the addition is completed; S3: adding 0.6 parts of triethylamine, maintaining the temperature at 92°C, and continuing to stir the reaction for 3 hours. After the reaction is completed, stop heating, let the mixture cool naturally to room temperature, pass the obtained product through a 400-mesh sieve to remove unreacted solid particles and other impurities, and then transfer it to a clean container, seal it and store it to avoid contact with air and moisture.

[0048] The preparation method of modified nanoparticles specifically comprises the following steps: S1: 1.8 parts of titanium dioxide and 4.6 parts of zinc nitrate hexahydrate are mixed and added to 120 parts of DMF, 1.6 parts of glutaric anhydride and 0.26 parts of tetraisopropoxy titanate are added, the temperature is raised to 75°C and kept warm for 2 hours, then ammonia water is added to adjust the pH to 8.4, then 0.06 parts of triethylamine, 0.5 parts of ethyl orthosilicate and 40 parts of ethanol are added, and the temperature is kept at 60°C for 2 hours. After the reaction is completed, the product is filtered and washed to obtain pre-modified particles; S2: 3.5 parts of pre-modified particles are added The mixture was added into 100 parts of DMF and mixed evenly, then 2.1 parts of 1,4-benzenedicarboxylic acid was added, and the mixture was stirred at 60 rpm for 25 min until uniform, then the temperature was raised to 85°C and kept warm for 1 hour, and then a DMF solution containing 0.75 parts of 1,4-diaminobenzene (15 parts in total) was added dropwise for 1 hour. After completion, the temperature of the reaction vessel was raised uniformly from 4°C to 120°C and kept warm for 16 hours. After the reaction was completed, it was naturally cooled to room temperature and the product was filtered, washed with deionized water and acetone 3 times, and dried in a vacuum oven at 80°C.

[0049] The average particle size of titanium dioxide is 12 nm; the average particle size of modified nanoparticles is 581 nm.

[0050] The anti-settling agent is hydrogenated castor oil; the leveling agent is silicone leveling agent BYK-333; the defoaming agent is silicone defoaming agent BYK-028; and the pigment filler is phthalocyanine blue.

[0051] The diluent is a composition of xylene and ethylene glycol monobutyl ether, and the mass ratio of the two is 5.5:2.

[0052] The second aspect of the present embodiment provides a method for preparing the above-mentioned epoxy resin coating resistant to chemical corrosion, which specifically includes the following steps: S1: adding the epoxy resin composition to a reactor with a stirring device, heating to 85°C, and continuously stirring at 100rpm until it is completely melted and uniform, and slowly adding modified nanoparticles, anti-settling agent, leveling agent and defoaming agent under stirring and continuing to stir for 35min to ensure that all solid particles are fully dispersed; S2: after adding the color filler, stirring at a high speed of 600rpm for 80min; S3: cooling to room temperature, slowly adding the curing agent, and continuously stirring for 25min, and finally adding the diluent to mix the coating. After completion, pass through a 500-mesh sieve, and fill the obtained product into a container and seal it for storage.

[0053] Example 2: The specific implementation method of this example is basically the same as that of Example 1, with the only difference being that the raw materials of the epoxy resin coating resistant to chemical corrosion, in parts by mass, are: 95 parts of epoxy resin composition, 22 parts of curing agent, 20.5 parts of modified nanoparticles, 3.9 parts of anti-settling agent, 1.8 parts of leveling agent, 1.2 parts of defoaming agent, 7.6 parts of pigments and fillers, and 30 parts of diluent.

[0054] The epoxy resin composition is a composition of bisphenol A epoxy resin, epoxy block resin and modified epoxy resin, and the mass ratio of the three is 70:10:15.

[0055] Example 3: The specific implementation method of this example is basically the same as that of Example 1, with the only difference being that the epoxy resin coating resistant to chemical corrosion, in parts by mass, comprises the following raw materials: 85 parts of epoxy resin composition, 18 parts of curing agent, 24 parts of modified nanoparticles, 4.0 parts of anti-settling agent, 1.6 parts of leveling agent, 1.1 parts of defoaming agent, 7.8 parts of pigment and filler, and 26 parts of diluent.

[0056] The epoxy resin composition is a composition of bisphenol A epoxy resin, epoxy block resin and modified epoxy resin, and the mass ratio of the three is 60:10:15.

[0057] Comparative Example 1 The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the epoxy resin coating resistant to chemical corrosion, in parts by mass, are: 120 parts of epoxy resin composition, 30 parts of curing agent, 12.5 parts of modified nanoparticles, 4.2 parts of anti-settling agent, 1.8 parts of leveling agent, 1.2 parts of defoaming agent, 8.5 parts of pigment filler, and 25 parts of diluent.

[0058] The epoxy resin composition is a composition of bisphenol A epoxy resin, epoxy block resin and modified epoxy resin, and the mass ratio of the three is 90:15:15.

[0059] Comparative Example 2 The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the epoxy resin coating resistant to chemical corrosion, in parts by mass, are: 75 parts of epoxy resin composition, 8.5 parts of curing agent, 35.5 parts of modified nanoparticles, 4.2 parts of anti-settling agent, 1.8 parts of leveling agent, 1.2 parts of defoaming agent, 8.5 parts of pigment filler, and 48 parts of diluent.

[0060] The epoxy resin composition is a composition of bisphenol A epoxy resin, epoxy block resin and modified epoxy resin, and the mass ratio of the three is 50:10:15.

[0061] Comparative Example 3 The specific implementation of this comparative example is basically the same as that of Example 1, except that the epoxy block resin is an ethylene oxide-propylene oxide block copolymer resin with a weight average molecular weight of 10,000 Da and an ethylene oxide block content of 80 wt%, purchased from L88 model product sold by BASF, Germany.

[0062] Comparative Example 4 The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified epoxy resin specifically includes the following steps: S1: adding 95 parts of the matrix epoxy resin E-44 into a reactor with a stirring device, heating to 90°C to make it completely melted, and then adding 450 parts of DMF and continuing to stir until it is evenly mixed; S2: slowly adding 10 parts of 4,4'-diaminodiphenyl ether while stirring at 90rpm, and continuing to stir for 30min after the addition is completed; S3: adding 0.3 parts of triethylamine, maintaining the temperature at 92°C, and continuing to stir the reaction for 3h. After the reaction is completed, stop heating, let the mixture cool naturally to room temperature, and pass the obtained product through a 400-mesh sieve to remove unreacted solid particles and other impurities, and then transfer it to a clean container, seal it and store it to avoid contact with air and moisture.

[0063] Comparative Example 5 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nanoparticles specifically comprises the following steps: S1: 0.6 parts of titanium dioxide and 4.6 parts of zinc nitrate hexahydrate are mixed and added to 120 parts of DMF, 1.6 parts of glutaric anhydride and 0.26 parts of tetraisopropoxy titanate are added, the temperature is raised to 75°C and kept warm for 2 hours, then ammonia water is added to adjust the pH to 8.4, then 0.02 parts of triethylamine, 0.2 parts of ethyl orthosilicate and 25 parts of ethanol are added, the temperature is kept at 60°C for 2 hours, and after the reaction is completed, the product is filtered and washed to obtain pre-modified nanoparticles. Particles; S2: Add 3.5 parts of pre-modified particles to 100 parts of DMF and mix evenly, then add 2.1 parts of 1,4-phthalic acid, stir at 60rpm for 25min until uniform, then heat to 85℃ and keep warm for 1h, then add DMF solution containing 0.75 parts of 1,4-diaminobenzene (15 parts in total) dropwise for 1h, after completion, heat the reaction container uniformly from 4℃ to 120℃ and keep warm for 16h, after the reaction is completed, naturally cool to room temperature and filter the product, wash with deionized water and acetone 3 times, and dry in a vacuum at 80℃ to obtain the product.

[0064] Comparative Example 6 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified nanoparticles specifically comprises the following steps: S1: 1.8 parts of titanium dioxide and 4.6 parts of zinc nitrate hexahydrate are mixed and added to 120 parts of DMF, 1.6 parts of glutaric anhydride and 0.26 parts of tetraisopropoxy titanate are added, the temperature is raised to 75°C and kept warm for 2 hours, then ammonia water is added to adjust the pH to 8.4, then 0.06 parts of triethylamine, 0.5 parts of ethyl orthosilicate and 40 parts of ethanol are added, and the reaction is kept warm at 60°C for 2 hours. After the reaction is completed, the product is filtered and washed to obtain the pre-modified nanoparticles. S2: Add 6 parts of pre-modified particles to 120 parts of DMF and mix evenly, then add 1.4 parts of 1,4-phthalic acid, stir at 60rpm for 25min until uniform, then heat to 85℃ and keep warm for 1h, then add DMF solution containing 0.32 parts of 1,4-diaminobenzene (10 parts in total) dropwise for 1h, after completion, heat the reaction container uniformly from 4℃ to 120℃ and keep warm for 16h, after the reaction is completed, cool naturally to room temperature and filter the product, wash with deionized water and acetone 3 times, and dry in a vacuum at 80℃ to obtain the product.

[0065] Comparative Example 7 The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of titanium dioxide is 30 nm; and the average particle size of the modified nanoparticles is 774 nm.

[0066] Performance Evaluation Corrosion resistance (salt spray) test: After the epoxy resin coatings prepared in the embodiments and comparative examples are cured, samples with a coating specification of 2cm×2cm×0.1cm are prepared. 5wt% NaCl is used as the test solution. The temperature conditions are 38±2°C and the relative humidity is 90±4%. The salt spray resistance test is carried out with an inclination angle of 20°, uniform spraying, a spray pressure of 1.5 bar, and a test time of 800h. After completion, observe whether there is bubbling, oxidation and cracking. If there is, it is unqualified, otherwise it is qualified. The qualified rate results of 50 groups of samples in each group are recorded in Table 1.

[0067] Temperature and humidity aging test: After the epoxy resin coatings prepared in the examples and comparative examples are cured, samples with a coating specification of 2cm×2cm×0.1cm are prepared and placed in a constant temperature and humidity chamber at 70±3°C and a relative humidity of 80±3% for 6 months. Afterwards, observe whether there are blistering, oxidation and cracking. If there are, it is unqualified, otherwise it is qualified. 50 groups of samples are tested in each group, and the qualified rate results are recorded in Table 1.

[0068] Waterproof test: After curing the epoxy resin coatings prepared in the embodiments and comparative examples, a sample with a coating specification of 2cm×2cm×0.1cm was obtained, a water droplet size of 2.5μL, and a time of 30s. The water contact angle of the coating surface was obtained, and the test value was the average of 10 tests and recorded in Table 1.

[0069] Color brightness test: The epoxy resin coatings prepared in the examples and comparative examples were coated on glass as a substrate and cured into coatings, and then brightness tests were performed. The coating thickness was 0.1 mm. A brightness meter was used to test the brightness of the coating. The test angle was 60°. The measured values ​​were taken as the average of 10 tests and recorded in Table 1.

[0070] Table 1 Performance test results

[0071] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 7 in terms of aging resistance, temperature resistance, corrosion resistance, water resistance, moisture resistance and coating brightness performance. This is mainly due to the combined effect of the modified nanoparticles, compounded epoxy resin composition and other matching technical solutions specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. An epoxy resin coating resistant to chemical corrosion, characterized in that: The epoxy resin coating resistant to chemical corrosion comprises, by weight, 80-100 parts of epoxy resin composition, 15-25 parts of curing agent, 15-25 parts of modified nanoparticles, 2-5 parts of anti-settling agent, 1-3 parts of leveling agent, 1-2 parts of defoaming agent, 5-10 parts of pigment and filler, and 20-40 parts of diluent; The epoxy resin composition is a composition of bisphenol A epoxy resin, epoxy block resin and modified epoxy resin; The mass ratio of the bisphenol A epoxy resin, epoxy block resin and modified epoxy resin is (60-70): (10-15): (10-15); The epoxy equivalent of the bisphenol A epoxy resin is 220-240 g / eq; The viscosity of the bisphenol A epoxy resin is 8000-12000 mPa·s at 25° C.; The preparation method of the modified nanoparticles is specifically The following steps are involved: S1: titanium dioxide and zinc nitrate hexahydrate are mixed and added to DMF, glutaric anhydride and tetraisopropoxy titanate are added, the temperature is raised to 75-80°C and kept warm for 2-2.5 hours, then ammonia water is added to adjust the pH to 8-8.5, then triethylamine, ethyl orthosilicate and ethanol are added, and the temperature is kept at 60-65°C for 1.5-2 hours. After the reaction is completed, the product is filtered and washed to obtain pre-modified particles; S2: Add the pre-modified particles to DMF and mix evenly, then add 1,4-benzenedicarboxylic acid, stir at 50-60 rpm for 20-30 min until evenly mixed, then heat to 80-90°C and keep warm for 1-1.5 h, then dropwise add the DMF solution containing 1,4-diaminobenzene for 1-1.5 h, after completion, heat the reaction vessel uniformly from 3-4°C to 110-130°C and keep warm for 14-16 h, after the reaction is completed, naturally cool to room temperature and filter the product, wash with deionized water and acetone 2-3 times, and dry under vacuum at 70-80°C, after completion, the product is obtained; The mass ratio of titanium dioxide, zinc nitrate hexahydrate, glutaric anhydride and tetraisopropoxy titanate is (1.5-2): (4-5): (1.5-2): (0.2-0.4); The mass ratio of titanium dioxide, zinc nitrate hexahydrate, triethylamine and ethyl orthosilicate is (1.5-2): (4-5): (0.05-0.1): (0.4-0.5); The mass ratio of the pre-modified particles, 1,4-phthalic acid and 1,4-diaminobenzene is (3-4): (1.8-2.2): (0.6-0.8).

2. The chemical-resistant epoxy resin coating according to claim 1, characterized in that: The mass ratio of the epoxy resin composition, the curing agent and the modified nanoparticles is (85-95): (18-22): (20-24).

3. The chemical-resistant epoxy resin coating according to claim 2, characterized in that: The epoxy block resin is an ethylene oxide-propylene oxide block copolymer resin; the weight average molecular weight of the epoxy block resin is 2000-4000Da.

4. The chemical-resistant epoxy resin coating according to claim 3, characterized in that: The epoxy block resin has an ethylene oxide block content of 30-35 wt %.

5. The chemical-resistant epoxy resin coating according to claim 4, characterized in that: The preparation method of the modified epoxy resin specifically comprises the following steps: S1: adding the matrix epoxy resin into a reaction kettle with a stirring device, heating it to 80-90°C to make it completely melted, then adding DMF and continuing to stir until it is evenly mixed; S2: slowly adding 4,4'-diaminodiphenyl ether with stirring at a speed of 80-100 rpm, and continuously stirring for 30-35 minutes after the addition is completed; S3: adding triethylamine, maintaining the temperature at 85-95°C, continuing to stir and react for 2-4 hours, and after the reaction is completed, stopping heating, allowing the mixture to cool naturally to room temperature, and passing the obtained product through a 400-600 mesh sieve to remove unreacted solid particles and other impurities, and then transferring it to a clean container, sealing it for storage, and avoiding contact with air and moisture; The mass ratio of the matrix epoxy resin, 4,4'-diaminodiphenyl ether and triethylamine is (60-70): (10-20): (0.5-1).

6. The chemical-resistant epoxy resin coating according to claim 5, characterized in that: The average particle size of the titanium dioxide is 10-15 nm; the average particle size of the modified nanoparticles is 550-650 nm.

7. The chemical-resistant epoxy resin coating according to claim 6, characterized in that: The anti-settling agent is at least one of fumed silica, hydrogenated castor oil, organic bentonite and polyamide wax.

8. The chemical-resistant epoxy resin coating according to claim 7, characterized in that: The leveling agent is at least one of an organic silicon leveling agent, a polyacrylate leveling agent, a polyether modified silicone oil leveling agent and a polyester leveling agent.

9. The chemical-resistant epoxy resin coating according to claim 8, characterized in that: The diluent is a composition of xylene and ethylene glycol monobutyl ether; the mass ratio of xylene to ethylene glycol monobutyl ether is (5-6): (1.5-2.5).

10. A method for preparing the epoxy resin coating resistant to chemical corrosion according to any one of claims 1 to 9, comprising the following steps: S1: Add the epoxy resin composition into a reactor equipped with a stirring device, heat to 80-90°C, and continue stirring at 80-120rpm until it is completely melted and uniform, and slowly add the modified nanoparticles, anti-settling agent, leveling agent and defoaming agent under stirring and continue stirring for 30-40 minutes to ensure that all solid particles are fully dispersed; S2: After adding pigments and fillers, stir at a high speed of 400-600 rpm for 60-80 minutes; S3: Cool to room temperature, slowly add curing agent, and continue stirring for 20-30 minutes, and finally add diluent to mix the coating. After completion, pass through a 400-600 mesh sieve, fill the obtained product into a container and seal it for storage.

Citation Information

Patent Citations

  • Moisture-proof, mildew-proof and corrosion-resistant current transformer coil coating and preparation method thereof

    CN118879161A

  • Thermoplastic resin coating as well as preparation method and application thereof

    CN118909495A

  • Antistatic environment-friendly automobile foot mat and preparation method thereof

    CN118994835A

Cited By

  • Waterproof and decorative integrated reflective heat-insulating waterborne polyurethane exterior wall coating and preparation method thereof

    CN119842303A

  • Waterproof decorative integrated reflective thermal insulation waterborne polyurethane exterior wall coating and preparation method thereof

    CN119842303B

  • Epoxy resin-based composition and application thereof in electronic packaging

    CN121293681A

  • An epoxy resin-based composition and its use in electronic encapsulation

    CN121293681B